Applicability of a drift-flux model of aerosol deposition in a test tunnel and an indoor heritage environment. (September 2016) - Grau-Bové, Josep; Strlič, Matija; Mazzei, Luca
Abstract: Near-wall turbulence associated with air flows parallel to walls can promote aerosol deposition. In indoor environments, where this kind of flow is frequently present, this results in local deposition gradients near ventilation inlets and outlets. This phenomenon is of special interest to the heritage field, which is often concerned about the spatial distribution of deposition and its links to environmental management. In this paper we investigate the capability of a drift-flux model of particulate matter deposition to describe this mechanism. This model has often been validated using decay rates of particulate matter concentration; however, in several indoor applications the interest is not in concentration but in the spatial distribution of the deposition flux. To test the model, we use untreated atmospheric aerosols in two different cases: an experimental tunnel designed to induce near-wall velocity gradients and an actual indoor room with various ventilation regimes. Both systems exhibit significantly inhomogeneous deposition distributions. While the first system is operated under controlled laboratory conditions, the second yields data collected in-situ during a six-month monitoring campaign. In either case the model reproduces the experimental values with enough accuracy to allow understanding how the environment behaves. This work confirms the usability of the drift-flux approach as an analysis tool for particle deposition in complex environments in a wide range of geometries. Highlights: We validate the drift-flux model for indoor heritage applications. We use data collected in a tunnel and an indoor environment. The experiments are carried out with common indoor aerosols. The data is well described with both transient and steady state simulations. We study the ability of the model to predict the spatial variation of deposition.